(untitled) (Estudios humanísticos. Geografía, historia y arte, 1998)
Throughout the Middle Ages, the administrative structures in the kingdom of Leon experiment many important changes, motivated by the inner evolution of the early medieval society, and also by the european and east-spaniard influence. For knowing better this complexe process, the historian must undertand and clarify before the concepts and terms by means of which that administrative reality are expressed.